An application of the Analytic Hierarchy Process for prioritizing user preferences in the design of a Home Energy Management System. (December 2018) - Kadavil, Rahul; Lurbé, Salvador; Suryanarayanan, Siddharth; Aloise-Young, Patricia A.; Isley, Steven; Christensen, Dane
Abstract: Most demand response programs focus primarily on commercial and industrial loads. The sheer number of decision-influencing variables combined with a lack of a comprehensive understanding of human behavior make it difficult to develop response programs that encourage greater residential consumer participation. This paper presents a multi-criteria decision making approach using actual survey data for identifying user preferences. The novelty of the work is in considering functionality, cost, and carbon emissions for a given set of home appliances toward energy management. The paper explains the design methodologies used to prioritize the preferences from 1023 survey participants. The results are expected to inform the design of Home Energy Management Systems (HEMS) for participating in demand response programs.